# If $ \left( {x + y} \right) = {45^ \circ } $ , then prove that:

(a) $ \left( {1 + \tan x} \right)\left( {1 + \tan y} \right) = 2 $

(b) $ \left( {\cot x - 1} \right)\left( {\cot y - 1} \right) = 2 $

Answer

Verified

280.5k+ views

**Hint**: The given question deals with basic simplification of trigonometric functions by using some of the simple trigonometric formulae such as $ \tan \left( {x + y} \right) = \dfrac{{\tan x + \tan y}}{{1 - \tan x\tan y}} $ and $ \cot \left( {x + y} \right) = \dfrac{{\cot x\cot y - 1}}{{\cot x + \cot y}} $ . Basic algebraic rules and trigonometric identities are to be kept in mind while doing simplification in the given problem.

**:**

__Complete step-by-step answer__In the given problem, we have to simplify and find the value of the given trigonometric expressions using compound angle formulae of tangent and cotangent.

Now, we are given the sum of two angles, x and y as $ {45^ \circ } $ .

First, we have to find the value of $ \left( {1 + \tan x} \right)\left( {1 - \tan x} \right) $ .

So, we know that $ \left( {x + y} \right) = {45^ \circ } $ .

Taking tangent on both sides of the equation, we get,

$ \Rightarrow \tan \left( {x + y} \right) = \tan {45^ \circ } $

Now, using the compound angle formula for tangent $ \tan \left( {x + y} \right) = \dfrac{{\tan x + \tan y}}{{1 - \tan x\tan y}} $ on the left side of the equation, we get,

$ \Rightarrow \dfrac{{\tan x + \tan y}}{{1 - \tan x\tan y}} = \tan {45^ \circ } $

We also know that the value of $ \tan {45^ \circ } $ is one. So, we get,

$ \Rightarrow \dfrac{{\tan x + \tan y}}{{1 - \tan x\tan y}} = 1 $

Cross multiplying the terms, we get,

$ \Rightarrow \tan x + \tan y = 1 - \tan x\tan y $

Shifting all the terms consisting of trigonometric functions to the left side of the equation, we get,

$ \Rightarrow \tan x + \tan y + \tan x\tan y = 1 $

Now, adding one to both sides of the equation, we get,

$ \Rightarrow \tan x + \tan x\tan y + \tan y + 1 = 2 $

Now, taking $ \tan x $ common from the first two terms and $ \tan y $ common from the last two terms in the left side of the equation, we get,

$ \Rightarrow \tan x\left( {1 + \tan y} \right) + \left( {1 + \tan y} \right) = 2 $

Factoring the equation, we get,

\[ \Rightarrow \left( {1 + \tan x} \right)\left( {1 + \tan y} \right) = 2\]

So, we get the value of \[\left( {1 + \tan x} \right)\left( {1 + \tan y} \right)\] as $ 2 $ .

Hence, proved.

Now, we also have to prove that $ \left( {\cot x - 1} \right)\left( {\cot y - 1} \right) = 2 $ .

Now, we have, $ \left( {x + y} \right) = {45^ \circ } $

Taking cotangent on both sides of the equation, we get,

$ \Rightarrow \cot \left( {x + y} \right) = \cot {45^ \circ } $

Now, using the compound angle formula for cotangent $ \cot \left( {x + y} \right) = \dfrac{{\cot x\cot y - 1}}{{\cot x + \cot y}} $ in the left side of the equation, we get,

$ \Rightarrow \dfrac{{\cot x\cot y - 1}}{{\cot y + \cot x}} = \cot {45^ \circ } $

We also know that the value of $ \cot {45^ \circ } $ is one. So, we get,

$ \Rightarrow \dfrac{{\cot x\cot y - 1}}{{\cot y + \cot x}} = 1 $

Cross multiplying the terms, we get,

$ \Rightarrow \cot x\cot y - 1 = \cot y + \cot x $

Now, shifting all the terms consisting of trigonometric functions to the left side of the equation and all the constants to the right side of equation, we get,

$ \Rightarrow \cot x\cot y - \cot y - \cot x = 1 $

Now, adding one to both sides of the equation,

$ \Rightarrow \cot x\cot y - \cot y - \cot x + 1 = 2 $

Now, taking $ \cot y $ common from the first two terms and negative sign common from the last two terms, we get,

\[ \Rightarrow \cot y\left( {\cot x - 1} \right) - \left( {\cot x - 1} \right) = 2\]

Factoring the equation, we get,

\[ \Rightarrow \left( {\cot x - 1} \right)\left( {\cot y - 1} \right) = 2\]

So, we get the value of \[\left( {\cot x - 1} \right)\left( {\cot y - 1} \right)\] as \[2\].

Hence, proved.

**Note**: Given problem deals with Trigonometric functions. For solving such problems, trigonometric formulae should be remembered by heart. Besides these simple trigonometric formulae, trigonometric identities are also of significant use in such types of questions where we have to simplify trigonometric expressions with help of basic knowledge of algebraic rules and operations. However, questions involving this type of simplification of trigonometric ratios may also have multiple interconvertible answers.

Recently Updated Pages

Which of the following would not be a valid reason class 11 biology CBSE

What is meant by monosporic development of female class 11 biology CBSE

Draw labelled diagram of the following i Gram seed class 11 biology CBSE

Explain with the suitable examples the different types class 11 biology CBSE

How is pinnately compound leaf different from palmately class 11 biology CBSE

Match the following Column I Column I A Chlamydomonas class 11 biology CBSE

Trending doubts

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

How many meters are there in a kilometer And how many class 8 maths CBSE

What is pollution? How many types of pollution? Define it

Change the following sentences into negative and interrogative class 10 english CBSE

What were the major teachings of Baba Guru Nanak class 7 social science CBSE

Difference Between Plant Cell and Animal Cell

Give 10 examples for herbs , shrubs , climbers , creepers

Draw a labelled sketch of the human eye class 12 physics CBSE